Genocide and resistance Nr. 54(2) - Jurkutė, Mingailė; Kripienė, Enrika; Staveckaitė-Notari, Ramona; Tumavičius, Andrius; Karaliūtė, Emilija; Indrišionis, Darius; Dreimane, Inese; Kaasik, Peeter; Latvytė, Neringa (Genocidas ir rezistencija, 2024)
-